2005
DOI: 10.1074/jbc.m407832200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of T Cell Death-associated Gene 8 (TDAG8) as a Novel Acid Sensing G-protein-coupled Receptor

Abstract: T cell death-associated gene 8 (TDAG8) is a G-proteincoupled receptor mainly expressed in lymphoid organs and cancer tissues. TDAG8 shares high amino acid sequence homologies with recently reported proton-sensing G-protein-coupled receptors, G2A, OGR1, and GPR4. Here we have identified TDAG8 as a novel proton-sensing receptor. Upon acid stimulation, stably expressed TDAG8 was internalized from the plasma membrane. As a signaling pathway downstream of TDAG8, accumulation of cyclic AMP was observed in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
150
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 170 publications
(161 citation statements)
references
References 35 publications
(31 reference statements)
8
150
0
Order By: Relevance
“…Interestingly, activation of G2A at low pH was antagonized by LPC. Furthermore, structurally similar GPCR, TDAG8, has also been reported to respond to acidic pH (26,27). Wang et al reported that the pH response of TDAG8 was antagonized by its ligand, psychosine, which also attenuated the activation of OGR1 and GPR4 at low pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, activation of G2A at low pH was antagonized by LPC. Furthermore, structurally similar GPCR, TDAG8, has also been reported to respond to acidic pH (26,27). Wang et al reported that the pH response of TDAG8 was antagonized by its ligand, psychosine, which also attenuated the activation of OGR1 and GPR4 at low pH.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they described that SPC and LPC do not exert any effects on the generation of second messengers. Subsequently, pH-dependent activation of G2A (25) and TDAG8 (26,27) was reported; Mu-rakami et al (25) showed that previously proposed ligand of G2A, LPC, inhibited pH-dependent accumulation of inositol phosphate in cells expressing G2A, whereas Wang et al (26) described that cAMP generation in TDAG8-expressing cells was inhibited by psychosine. The latter authors also demonstrated that psychosine acts antagonistically to the pH-dependent generation of second messengers in GPR4-or OGR1-expressing cells.…”
mentioning
confidence: 99%
“…For example, stimulation of OGR1 results in the activation of phospholipase C/Ca 2ϩ mobilization (12,13,18), and the stimulation of TDAG8 and GPR4 causes the activation of adenylyl cyclase/AMP accumulation (12,(15)(16)(17)(18). We therefore examined which OGR1 family receptors are expressed in mouse macrophages.…”
Section: Tdag8 Partly Mediates Acidification-induced Inhibition Of Tnmentioning
confidence: 99%
“…However, the signaling mechanism remains unknown. TDAG8 has been shown to be coupled to multisignaling pathways, including the G s protein/cAMP pathway and the G 12/13 protein/ pathway (15,16,18). To examine whether cAMP accumulation occurs by acidification in macrophages, we tried to measure the cellular cAMP content under the same experimental condition as that for cytokine production.…”
Section: Involvement Of G S Proteins and A Camp/protein Kinase A Pathmentioning
confidence: 99%
See 1 more Smart Citation